Minding Mental Health in Disaster Risk Reduction and Management: Enhancing Resistance Through Disaster Prevention, Mitigation, and Preparedness - Labaria, Elirozz Carlie D (Archīum Ateneo, 2020)
Although the Sendai Framework for Disaster Risk Reduction 2015–2030 explicitly recognizes the need for psychosocial support and mental health services, the focus of this and many disaster risk reduction and management (DRRM) plans lies in the response, recovery, and rehabilitation phases. Less attention has been given to how mental health aspects affect the predisaster phase. This chapter explores the less understood concept of “resistance” in the perspectives model of disaster mental health, which is related to DRRM themes of “prevention and mitigation” and “preparedness” interventions. Four strategies are identified by which DRRM interventions can contribute to psychosocial support and mental health: increasing stress resistance, fostering cohesion and social support, fostering positive cognition, and building self-efficacy and hardiness. We review the cases of the Philippines, Indonesia, Myanmar, and Thailand and report existing socio-political DRRM initiatives for prevention, mitigation, and preparedness that can potentially enhance resistance as a predisaster intervention. Beyond medical services or clinical mental health interventions for select populations, DRRM interventions can benefit the general public. Despite natural intersections, there remains a need for deliberate and targeted initiatives that explore how vertical pyschosocial care programs can be created to straddle both DRRM and health sectors in practice.